Assessing maximum loads when skidding wood uphill with tractors - Košir, Boštjan (Zbornik gozdarstva in lesarstva, 2008)
The results of measuring maximum loads on different slopes when skidding uphill with WOO DY 110 cable skidder and adapted 4WD agricultural tractor AGT 835 are described in the article. Both tractors are very different and were chosen for the purpose of finding the limits of uphill skidding. Besides the slope, the pre-designated loads of different sizes and log orientation (butt-end or top-end forward) have been main variables. The trial was conducted on two concave shaped test skid trails in the forest. On the lower altitudes, the skid trails had small inclination, which slowly increased to 42% on the track where WOODY 110 was tested, and 27% where AGT 835 was measured. First the loads were skidded uphill with butt-end and then with top-end forward. The purpose was to choose too heavy loads, as we wished to stop tractors due to overload, but on different slopes. The proper load formation (butt-end forward if possible) in uphill skidding is most important on steeper skid trails. The dependency between maximum load and slope is linear. The calculated theoretical maximum load on horizontal surface enables us to make similar assessment for any other tractor weighing between 2 and 7 tons. For this purpose, John Deere 6220 and LIMB 80 LUXS adapted agricultural tractors for forest use were chosen and compared. The ratio between the tractor load on different slopes and tractor weight was calculated for all four tractors included in our comparison. Apart from the weight, tractor's engine torque (power) has the decisive influence on the load size. Maximum loads on different slope categories were calculated according to different engine powers.
Keywords: obremenitve; spravilo lesa; traktorji